Noradrenergic response in vas deferens from rats submitted to acute and repeated stress - Pereira, OCM; Dega, M. R.; Souza, MSS (Elsevier B.V., 1998)
1. This work investigated the effects of androgens on the norepinephrine sensitivity of vasa deferentia from rats submitted to acute or repeated stress, as well as the participation of alpha(1)-adrenoceptors in the response of intact and bisected vasa deferentia from adult normal rats submitted to acute or repeated stress.2. The acute stress produced subsensitivity to norepinephrine only in intact vasa deferentia from adult normal rats, which was prevented by lack of androgens, suggesting that the sensitivity may be dependent on the physiological level of androgen,3. No change was observed in intact vas deferens sensitivity to norepinephrine in repeated stress, suggesting the occurrence of adaptation to elevated norepinephrine levels or a mild decrease in androgen levers or both.4. The changes in sensitivity observed in acute and repeated stress may also be due to alterations in alpha(1)-adrenergic receptors that are located in the prostatic portion of the vas deferens. (C) 1998 Elsevier B.V.
Keywords: swimming stress; vas deferens; norepinephrine; prazosin; rat